Federica Buttò, Le « Tristan en prose » du ms. BnF français 756 : texte et étude - Federica Buttò (Perspectives Médiévales)
Sixteen years after the last publication of a volume of the Tristan en prose (2007), this work completes this edition based on the manuscript Paris, Bibliothèque nationale de France, français 757, by making available the first half of the prose romance contained in codex Paris, Bibliothèque nationale de France, français 756. As well as making available the text of an important witness, this thesis highlights new links between certain codices of the manuscript tradition, provides additional information on the witnesses used for the collation and sheds light on the history of the manuscript Paris, Bibliothèque nationale de France, français 756 (illuminators, owners, clients, methods and time of production, etc.) and contributes to linguistic work on franco-Italian and “Naples French”. All this has been made possible by an interdisciplinary approach combining palaeography, codicology, history, philology, literature and linguistics. In this way, the thesis opens new research perspectives about the manuscript tradition of the Tristan in prose, which remains an open and promising field of investigation that shows a lively reception of Arthurian literature in Italy.